Improved low temperature NH3-SCR performance of FeMnTiOx mixed oxide with CTAB-assisted synthesis. Issue 16 (28th January 2015) - Wu, Shiguo; Yao, Xiaojiang; Zhang, Lei; Cao, Yuan; Zou, Weixin; Li, Lulu; Ma, Kaili; Tang, Changjin; Gao, Fei; Dong, Lin
Abstract : Transformation of anatase into rutile was inhibited by CTAB during preparation, and caused excellent low-temperature performance in NH3 -SCR. Abstract : FeMnTiO x mixed oxide is prepared by the CTAB-assisted co-precipitation method, and the transformation of anatase into rutile is inhibited by CTAB to some extent. The catalyst obtained in the present work shows nearly 100% NO conversion at 100–350 °C, more than 80% N2 selectivity at 75–200 °C, and excellent H2 O durability for the selective catalytic reduction of NO by NH3 with a space velocity of 30 000 mL g −1 h −1 .